Cardiovascular Pulsatility Increases in Visual Cortex Before Blood Oxygen Level Dependent Response During Stimulus - Huotari, Niko; Tuunanen, Johanna; Raitamaa, Lauri; Raatikainen, Ville; Kananen, Janne; Helakari, Heta; Tuovinen, Timo; Järvelä, Matti; Kiviniemi, Vesa; Korhonen, Vesa (Frontiers in Neuroscience, 2022)
The physiological pulsations that drive tissue fluid homeostasis are not well characterized during brain activation. Therefore, we used fast magnetic resonance encephalography (MREG) fMRI to measure full band (0 – 5 Hz) blood oxygen level-dependent (BOLDFB) signals during a dynamic visual task in 23 subjects. This revealed brain activity in the very low frequency (BOLDVLF) as well as in cardiac and respiratory bands. The cardiovascular hemodynamic envelope (CHe) signal correlated significantly with the visual BOLDVLF response, considered as an independent signal source in the V1-V2 visual cortices. The CHe preceded the canonical BOLDVLF response by an average of 1.3 (± 2.2) seconds. Physiologically, the observed CHe signal could mark increased regional cardiovascular pulsatility following vasodilation.